2016
DOI: 10.1073/pnas.1515152113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for m7G recognition and 2′-O-methyl discrimination in capped RNAs by the innate immune receptor RIG-I

Abstract: RNAs with 5′-triphosphate (ppp) are detected in the cytoplasm principally by the innate immune receptor Retinoic Acid Inducible Gene-I (RIG-I), whose activation triggers a Type I IFN response. It is thought that self RNAs like mRNAs are not recognized by RIG-I because 5′ppp is capped by the addition of a 7-methyl guanosine (m7G) (Cap-0) and a 2′-O-methyl (2′-OMe) group to the 5′-end nucleotide ribose (Cap-1). Here we provide structural and mechanistic basis for exact roles of capping and 2′-O-methylation in ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
341
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(372 citation statements)
references
References 30 publications
10
341
2
2
Order By: Relevance
“…The N-7-methylation of the viral RNA cap by ZIKV NS5-MTase allows recognition by the translation initiation factor eIF4E and stimulation of translation into viral proteins (8). On the other hand, 2=-O-methylation of the cap is expected to mask the presence of exogenous viral RNAs from host cell sensors such as RIG-I and MDA5 (9)(10)(11), which induce the production of interferons. In addition, 2=-O-methylation of viral RNA is thought to prevent translation restriction by interferon-stimulated genes (ISGs) such as the IFIT-1 gene (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-7-methylation of the viral RNA cap by ZIKV NS5-MTase allows recognition by the translation initiation factor eIF4E and stimulation of translation into viral proteins (8). On the other hand, 2=-O-methylation of the cap is expected to mask the presence of exogenous viral RNAs from host cell sensors such as RIG-I and MDA5 (9)(10)(11), which induce the production of interferons. In addition, 2=-O-methylation of viral RNA is thought to prevent translation restriction by interferon-stimulated genes (ISGs) such as the IFIT-1 gene (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The N-7 methylation of the cap structure is essential for RNA stability and stimulates their translation into viral protein by recognizing the translation initiation factor eIF4E (8). The 2=-O-methylation of the cap structure was demonstrated to protect viral RNA from being recognized by host cell sensors such as RIG-I and MDA5 that stimulate the production of interferons (9)(10)(11). In turn, interferon-stimulated genes, such as IFIT-1, can detect miscapped RNA and restrict their translation into proteins (12,13).…”
mentioning
confidence: 99%
“…In different eukaryotes the levels of cap-0, cap-1, and cap-2 in mRNA vary. The amount of methylation has increased during evolution (Banerjee 1980) and is implicated in immunogenicity (Daffis et al 2010;Devarkar et al 2016).…”
Section: Thementioning
confidence: 99%
“…This is especially reflected in the low number of structures of proteins in complex with capped RNA (>1 nt) that have been determined to date. Currently, these structures include the human 2 ′ -O-ribose methyltransferase CMTr1 with a capped 4-mer that was produced by chemical coupling (Smietanski et al 2014), the 2 ′ -O-ribose methyltransferase of vaccinia virus with a capped 6-mer that was produced by in vitro transcription in the presence of a cap analog (Hodel et al 1998), the 2 ′ -O-ribose methyltransferase in the NS5 protein from dengue virus with an 8-mer cap-0 viral RNA that was produced using a cap analog (Zhao et al 2015), the dengue virus methyltransferase in complex with a 5 ′ -capped RNA 8-mer that was chemically synthesized (Yap et al 2010), and the innate immune receptor RIG-I that contains a chemically synthesized 24-nt-long capped hairpin RNA (Devarkar et al 2016). The high-resolution structural data available is thus confined to a small subset of the numerous enzymes and proteins that directly interact with the mRNA cap structure.…”
Section: Thementioning
confidence: 99%
“…For a long time, it was unclear why the 5 0 end of mRNAs would undergo such extensive methylation. Recent studies have revealed that 2 0 -O methylation of cellular RNA plays a central role in discrimination of self from non-self RNA, e.g., distinction of viral from host RNA [10,11], while reversible interconversion of N6, 2 0 -Odimethyladenosine and 2…”
mentioning
confidence: 99%